Ganoderma lucidum total triterpenes attenuate DLA induced ascites and EAC induced solid tumours in Swiss albino mice - Smina, T P; Mathew, J; Janardhanan, K K (Cellular and Molecular Biology, 2016)
G. lucidum total triterpenes were assessed for its apoptosis-inducing and anti-tumour activities. The ability of the total triterpenes to induce apoptosis was evaluated in Dalton’s lymphoma ascites (DLA) and Ehrlich’s ascites carcinoma (EAC) cell lines. Total triterpenes were found to be highly cytotoxic to DLA and EAC cell lines with IC50 values 5 ± 0.32 and 7.9 ± 0.2 µg/ml respectively. Total triterpenes induced apoptosis in both cell lines which is evident from the DNA fragmentation assay. Anti-tumour activity was accessed using DLA induced solid and EAC induced ascites tumour models in Swiss albino mice. Administration of 10, 50 and 100 mg/kg b. wt. total triterpenes showed 11.86, 27.27 and 40.57% increase in life span of animals in ascites tumour model. Treatment with 10, 50 and 100 mg/kg b. wt. total triterpenes exhibited 76.86, 85.01 and 91.03% inhibition in tumour volume and 67.96, 72.38 and 77.90% inhibition in tumour weight respectively in the solid tumour model. The study reveals the significant dose-dependent anti-tumour activity of total triterpenes in both models. Total triterpenes were more active against the solid tumour than the ascites tumour. The anti-oxidant potential and ability to induce cell-specific apoptosis could be contributing to its anti-tumour activities.